Tembang Macapat: Kritik Sosial Sedulur Sikep terhadap Ekspansi Industri Semen di Pegunungan Kendeng - Iriyanto, Ery (Sutasoma : Jurnal Sastra Jawa, 2020)
Macapat song is an ancestral heritage that contains life guidance for the Javanese. Each lyric or cakepan of the Macapat song has a deep meaning. However, for Sedulur Sikep Sukolilo Pati, the macapat song was used as a social criticism of the plan to build a cement factory in the Kendeng Utara mountains. Cakepan macapat song is adapted to the social criticism that is to be conveyed through the song. This research uses literary criticism studies (expressive criticism) with a descriptive analysis approach. The research data is in the form of cakepan tembang macapat. Sources of research data, namely Sedulur Sikep figures and social media. Methods of data collection using observation, interviews, and documentation. Data analysis using data reduction techniques, data presentation, and data verification. The results showed that the social criticism used by Sedulur Sikep through the macapat song consisted of five Pangkur songs and one Dhandhanggula song. The social criticisms include, 1) farmers land planted with cement factories, 2) justice must be upheld, 3) casualties caused by miners, 4) the government torments farmers, 5) the earth begins to prosecute nature destroyers, 6) commemoration of earth day is useless. Keywords: macapat song, social criticism, Sedulur Sikep, cement industry, Kendeng mountains.